Human Capital and Social Capital as Determining Factors of The Msmes Surviving Ability - Safii, Abdul Azis; Rahayu, Susilowati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
This study aims to analyze human capital and social capital factors that can help Batik Bojonegoro MSME to survive. Data were collected from 247 MSMEs of Bojonegoro Typical Batik producers. 105 MSMEs are still operating, while the remaining 142 MSMEs are no longer producing Jonegoroan Batik. The data were obtained through a survey on 2020. With the probit model estimation, the analysis shows that the level of education, business experience, family, number of colleagues, and family business networks has a positive influence on the ability to survive the Bojonegoro batik MSMEs. The research also found that the level of education strengthens the influence of the number of colleagues, and family business networks on the survival of MSMEs.